NÖROPATİK AĞRI TEDAVİSİNDE FİZİK TEDAVİ AJANLARININ ETKİSİ - YILDIRIM, ARAFE (Fırat Üniveristesi, 2007)
Uluslararası agrı çalısma birligi nöropatik agrıyı (NA) sinir sisteminde primer bir lezyon veya disfonksiyonun neden oldugu veya baslattıgı agrı olarak tanımlamaktadır. Tedavisi güç agrı sendromları arasında bulunan NA'da bazı durumlarda yeterli tedavi saglanamamaktadır. Bu çalısmadaki amacımız NA tedavisinde fizik tedavi ajanlarının etkilerini arastırmaktır. Çalısmaya 2 hasta grubu alındı. Diyabetik periferik nöropatik agrılı (DPNA) 45 hasta ve kompleks bölgesel agrı sendromu (KBAS) tip1'li 5 hasta alındı. DPNA'lı çalısma grubuda 2 alt gruba ayrıldı. 23'ünün ayak tabanlarına %0.5 CaCI2 iyontoforezi ve 22'sine galvanik akım verildi. Hastaların hepsinin tedavi öncesi (TÖ) ve sonrası NA skalası (NAS), Stanford Saglık Degerlendirme Anketi (HAQ), LANSS agrı skalası, 50 m yürüme süresi, vizüel analog skala kullanılarak uyku kalitesi (VAS-UK) degerleri karsılastırıldı. KBAS tip1'li 5 hastanın etkilenen taraf stellat gangliyonuna ultrason (US) uygulandı. Cilt ısısı, mobilite kaybı, VAS-UK, NAS, ve LANSS agrı skalası TÖ ve sonrası degerlendirildi. DPNA alt gruplarında TS VAS-UK, LANSS agrı skalasında anlamlı düzelme görüldü. %0.5 CaCI2 iyontoforez grubunda HAQ'da düzelme oldu. Yürüme süresinde düzelme 2 alt grupda da izlenmedi. %0.5 CaCI2 iyontoforez grubunda NAS' da 8 maddede, galvanik akım grubunda 6 maddede düzelme oldu. Alt gruplar agır ve hafif olarak ayrıldıgında hafif gruplarda daha belirgin düzelmeler görüldü. KBAS tip1 hastalarda TÖ ve sonrasında cilt ısılarında ve LANSS agrı skalasında düzelme olmadı. Mobilite kaybında, VAS-UK, HAQ ve NAS `ın 2 maddesinde düzelme oldu. Bu çalısmadaki sonuçlarımız DPNA tedavisinde %0.5 CaCI2 iyontoforezinin galvanik akıma göre üstün oldugunu, fakat hafif nöropatili grupta etkinliginin daha fazla oldugunu gösterdi. Yine KBAS tip1 tedavisinde stellat gangliyona US tedavisinin yararlı olabilecegini gösterdi. Anahtar kelimeler: Nöropatik agrı, periferik diyabetik nöropatik agrı, CaCI2 iyontoforezi, kompleks bölgesel agrı sendromu, stellat gangliyon blokaj

Neuropathic pain has been defined by the International Association for the Study of Pain as pain initiated or caused by a primary lesion or dysfunction in the nervous system. In neuropathic pain, often considered as a difficult pain syndrome, enough pain reduction could not be achieved. The aim of this study was to assess the efficacy of physical therapy in the management of neuropathic pain. Two groups of patients, first group consisting 45 patients with diabetic peripheral neuropathic pain and second group consisting 5 patients with complex regional pain syndrome (CRPS), were included into the study. Diabetic peripheral neuropathic pain group were divided into 2 subgroups. 0.5% CaCl2 iontophoresis therapy to the sole was given to 23 patients and galvanic current was given to 22 patients. All of the patients were assessed at baseline and after treatment for neuropathic pain scale (NPS), Stanford Health Assessment Questionnaire (HAQ), Leeds assessment of neuropathic symptoms and signs pain scale (LANSS pain scala), 50 m walking time, and sleep quality using visual analogue scale. Second group consisted of five patients with CRPS. Patients were treated with ultrasound to the effected stellate ganglion. Cutaneous temperature were measured pre- and post-treatment. Also loss of mobility, NPS, LANSS pain scale and sleep quality using VAS were assessed at baseline and after treatment. In the subgroups of diabetic peripheral neuropathic pain significant improvements were achieved both in sleep quality and in LANSS pain scale with the treatment. HAQ improved significantly only in 0.5% CaCl2 ionthophoresis group, however 50 m walking time did not change in both of the subgroups of diabetic peripheral neuropathic pain. In 0.5% CaCl2 group 8 item of NPS and in galvanic current group 6 item of NPS significantly improved. However when the subgroups were divided as mild and severe, significant improvements were seen in mild groups. Pre and post-treatment changes in cutaneous temperature and LANSS pain scale were not significant in CRPS group. In CRPS group significant improvement was achieved in sleep quality, HAQ, mobility loss, and 2 items of NPS. Our results revealed that 0.5% CaCl2 ionthophoresis is superior to galvanic current in diabetic peripheral neuropathic pain however much more effective in mild neuropathic groups. Also our results revealed that stellat ganglion US treatment may have beneficial effects. Key Words: Neuropathic pain, diabetic peripheral neuropathic pain, CaCl2 ionthophoresis, complex regional pain syndrome, stellat ganglion block.
Efficacy of physical therapy modalities in neuropathic pain management
Keywords: Fiziksel Tıp ve Rehabilitasyon